The Spirituality of Kawruh Begja to Achieving the Reality of Life According to Ki Ageng Suryamentaram - Mulyatno, CB. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study focuses on analyzing the spirituality of Kawruh Begja for the realization of the authenticity of life based on the life and thoughts of Ki Ageng Suryamentaram. To explore the data used qualitative analysis methods and literature study. This study aims to find aspects of Kawruh Begja's spirituality in the study of cultural philosophy. Sebastian Painadath's thoughts on spirituality and its aspects were used as a framework for collecting data and analyzing it. The result of this research is the discovery of the notion of spirituality and its aspects in Kawruh Begja. In Ki Ageng Suryamentaram's meaning of life movement, Kawruh Begja is a system of philosophy and spirituality that encourages the process of living together to achieve the authenticity of life. Kawruh Begja are also values that are believed and lived which include awareness of the mysteries of life, understanding of life as a whole, personal spiritual experience, spiritual discipline, sensitivity to a harmonious environment, and compassion and concern for living together.